Produktivitas Rumput Hamil (Panicum maximum cv Hamil) yang Ditanam Menggunakan Benih Berbeda - Ahmad Fanindi; Endang Sutedi; Harmini Harmini (Institut Pertanian Bogor, 2021)
Reproductive traits determine the selection method in plant breeding. The benggala grass of the Hamil cultivar was thought to be apomictic; thus, a study was conducted to determine its reproduction. The research began by studying the morphological characters, continued with observing the generative phase and seed production of the cultivar planted from seeds (generative) and from pols (vegetative). The experiment was conducted in the greenhouse of the Research Institute of Animal Production. The experimental design was a completely randomized design with ten replications, and the treatments were different types of plant materials: seeds and pols. The Hamil cultivar taken from RIAP Collection was planted in pots with a diameter of 40 cm and a height of 30 cm. The results showed that most of the morphological characters of the Hamil cultivar planted from seeds and from pols were not different (P >0.05), so it was presumed that they were apomictic. The difference in morphology was only in the length and width of the flag leaves and the length of the internodes, where the cultivars planted using seeds were higher. The production of seeds, pithy seed weight, and seed germination of cultivars planted using seeds were higher (P <0.05). Further research is needed to determine the apomixis properties based on cytologically Hamil cultivars. Keywords: apomixis, benggala grass, morphology, plnting material; seed